2021
DOI: 10.3390/buildings11060249
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Adopting Building Information Modeling (BIM) in Sustainable Building Projects—A Case of Malaysia

Abstract: In terms of sustainable growth, Malaysia’s construction industry faces significant challenges, such as construction costs and lack of awareness. To meet these challenges, it is essential to integrate building information modeling (BIM) and sustainable development. As a result, this study aimed to establish strategies for adopting BIM in sustainable building projects. A systematic literature review was performed to classify the strategies to accomplish this aim, followed by a questionnaire survey of 129 constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…This has also been highlighted by Wong et al [43] as providing comprehensive training programs will increase BIM acceptability and subsequently boost productivity. Manzoor et al [44] suggested offering more concrete information about BIM cost and benefits will facilitate sustainable buildings development.…”
Section: Challenges Of Bim Implementation In Building Projectsmentioning
confidence: 99%
“…This has also been highlighted by Wong et al [43] as providing comprehensive training programs will increase BIM acceptability and subsequently boost productivity. Manzoor et al [44] suggested offering more concrete information about BIM cost and benefits will facilitate sustainable buildings development.…”
Section: Challenges Of Bim Implementation In Building Projectsmentioning
confidence: 99%
“…The construction industry benefits society in ways other than profit, health, and wellbeing. It has significant effects on community services while enhancing individuals' quality of life and safety [16]. Manzoor et al [16] considered the sustainable development of the construction industry in Malaysia and examined the effects of resources used in construction projects on project objectives.…”
Section: Project Schedulingmentioning
confidence: 99%
“…It has significant effects on community services while enhancing individuals' quality of life and safety [16]. Manzoor et al [16] considered the sustainable development of the construction industry in Malaysia and examined the effects of resources used in construction projects on project objectives. Harirchian and Lahmer [17] showed that the resources used in the project affect the resilience and safety and other goals of the project such as time and cost.…”
Section: Project Schedulingmentioning
confidence: 99%
“…Many developed and developing countries have specific building energy and design requirements based on their respective environments and climates that meet, among other criteria, their respective design and construction method requirements [27]. Since architects and engineers believe that greater energy efficiency in buildings starts with design, the majority of them stay motivated with respect to their building designs in advance and work to design measures to achieve sustainable goals [28]. In terms of improved sustainability and energy efficiency, for example, research showed that homebuyers want more energy and resource efficiency, but they lack effective contact with builders, there is insufficient knowledge, and their choices are too small [29].…”
Section: Introductionmentioning
confidence: 99%